Improving Chinese College Students’ Argumentative Writing: A Presentation-Assimilation-Discussion-Exercise Approach - Liao, Menglin; Liao, Yuanxi (Frontiers in Psychology, 2022)
This study implemented the Presentation-Assimilation-Discussion-Exercise (PADE) model, a student-centered teaching model originated in China, and examined its effect in college students’ argumentative writing. Quantitative method was used in this study following teaching practice of 14 weeks. 76Chinese first-year university students of intermediate English level with 38 students in an experimental class and 38 students in a comparison class took part in the study. Students from the experimental class received the Presentation-Assimilation-Discussion-Exercise (PADE) model and the comparison class received traditional teaching. Students from both classes were asked to compose two argumentative essays before and after treatment. At the end of treatment, students completed questionnaires on the Presentation-Assimilation-Discussion-Exercise (PADE) teaching model. Students’ writings were evaluated on aspects of linguistic quality and argumentative structure. The results indicated that students who learned in the Presentation-Assimilation-Discussion-Exercise (PADE) teaching environment outperformed students who followed traditional teaching method in the post-writing, and a significant difference was shown on all aspects except organization. The questionnaire finding suggested that students from the experimental class held a welcoming attitude toward the Presentation-Assimilation-Discussion-Exercise (PADE) model and benefited from the Presentation-Assimilation-Discussion-Exercise (PADE) model on the perspectives of course design, teaching arrangement and learning effect. The Presentation-Assimilation-Discussion-Exercise (PADE) teaching have implications for teaching writing in contexts that share much similarity.